Development Of Smojo.Ai Website-Based Math Learning Media On the Topic of 3D Flat Shapes To Improve Student Learning Outcomes - Ihsanudin, Ihsanudin; Rafianti, Isna; Ardini, Anggi; Pamungkas, Aan Subhan (Prima: Jurnal Pendidikan Matematika, 2024)
Student learning outcomes in the field of mathematics are still relatively low with several contributing factors such as the quality of teachers, the use of technology and the lack of understanding of basic mathematical concepts. Teachers can improve student learning outcomes by utilizing technology-based learning materials. One of the media that can be used is website-based learning media, namely media that provides learning materials, learning activities and various other supporting features to support the learning process. Smojo.Ai is an example of website-based learning media that can be used by teachers in the classroom. This study aims to produce a smojo.ai website-based math learning media product on the topic of 3D flat shapes that is feasible, effective and can improve student learning outcomes in the cognitive aspect. The results showed that the learning media products produced were categorized as feasible to use based on the validation assessment by media experts with a percentage assessment of 80% with a good category and an assessment by material experts with a percentage assessment of 89.4% with a very good category. The resulting media product is considered effective based on the results of the teacher practicality test assessment and student response questionnaire with a score of 95% and 86.25% with a very practical category. This learning media product is also proven to be able to improve student learning outcomes on cognitive aspects with an average pre-test score of 34.86 and an average post-test score of 74.89.